Effects of student centered teaching module on knowledge and learner development in pathophysiology subject among nursing students - Tongnuang, Patcharawadee (2010)
The purpose of this research was to examine the effects of student center teaching modules on learner knowledge and learner developments into three aspects: social skills, self development, and equality acceptance. These three aspects were examined from a Pathophysiology point of view. This study included a sample size of 106 students in the first - semester of the 2008 academic year pursing their bachelor’s degree in Nursing. The research instruments used were a Pathophysiological knowledge test, and a learner developments questionnaire. This study consisted of five modules instruction including; lecture discussion, mind mapping, case study, group discussion and cooperative learning.The results showed that overall the three key aspects studied in each of the five teaching modules was: social skills, self development, and equality acceptance were at a high level, while the cooperative learning module had the highest rating and the lecture discussion module had the lowest rating. The top rated key aspects for the cooperative learning module were self development and equality acceptance, while the top rated key aspect for the lecture discussion was social skill. Furthermore, there was a significant difference in the scores between the pre teaching methods and the proposed teaching methods researched in this study.